Legitimizing Sexual Predators in the 2025 Draft Criminal Procedure Code - Sepmiko, Jorza; Syauket, Amalia; Sihombing, Hubertus L.; Kusuma, Jaya; Irwan (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
This paper analyzes a legal loophole in Law No. 1 of 2023 concerning the Indonesian Criminal Code (KUHP) related to the exemption from criminal responsibility for persons with mental disabilities (Article 67 juncto Article 64 paragraph (1) letter c, Article 103, Article 38, and Article 39). This loophole has the potential to be misused by sexual offenders, such as sexual predators with paraphilic disorders, to avoid imprisonment and only receive action-based sentencing in the form of rehabilitation or even absolute acquittal. This research uses a normative method with criminological and victimological approaches. The findings indicate that the convergence between the provisions of the 2023 KUHP and the 2025 Draft Criminal Procedure Code (KUHAP), particularly Article 45 concerning the temporary suspension of investigations and diversion mechanisms, has the potential to cause the